Schools and Teachers in the USSR - Frank C. Johnstone; Claire Molloy (University of Aberdeen, School of Education, 2016)
I was drawn to Schools and Teachers in the USSR by Frank C. Johnstone from Volume 6 1969 as Soviet history is an area of interest to me. I was fascinated to hear of descriptions of the developing 'Kindergartens' originally set up by factories and collective farms to look after children whilst their mothers worked. Now (in 1969) the government were taking over this role, looking after children aged 3 to 7 (nurseries take them up to 3 and they start school at 7), in places that were open 24/7 staffed by teachers, assistants, 'domestics' nurses and a part time doctor! The idea of nurturing and developing the pre-school child is not new! In the USSR children all had to learn a language, usually from age 12. Johnstone visited a special language school where children started to learn that second language from age 9. He observed science and maths lessons being taught in the language being studied - CLiL in 1969 Moscow! He says that it is difficult to find subject specialists with the additional language skills and that teacher training establishments are encouraging anyone that shows linguistic skills to stay on a additional year to build on these. A lesson to be learned today? I was fascinated by the idea of all children being expected to participate in some 'socially helpful work' (active citizens?) and that all children and parents were involved in the behaviour of students, with any 'delinquent' being brought up in front of the pupil council and, for particularly serious issues, one including parents. The idea of such pupil/parental involvement in the school running very much parallels the talk of today if not the action. In all a wonderful insight into a bygone era that very much talks to today.